2016
DOI: 10.3153/jaefr16016
|View full text |Cite
|
Sign up to set email alerts
|

THE OCCURRENCE OF Ligula intestinalis IN ITS FISH HOST Rutilus rutilus (L.) AND THE EFFECTS OF PARASITE ON THE FISH GROWTH (BÜYÜKÇEKMECE RESERVOIR, TURKEY)

Abstract: Abstract:Roach Rutilus rutilus (Linnaeus, 1758) is a very common fish species for Turkish inland waters, especially in Büyükçekmece Reservoir (İstanbul). The species is one of the most caught fish species and holds economic consumption value even though it is mostly infected by Ligula intestinalis (Linnaeus, 1758), a pseudophyllidean cestode causing severe pathological effects on fishes. The aim of the study was to determine the presence of L. intestinalis plerocercoids in its fish host R. rutilus and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…However, based on the annual examinations according to the years, it is seen that infestation can be seen in any month of any season. Similar to the sampling period in this study, it was reported that L. intestinalis infestation was seen intensively in July, August, and September (Saç et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, based on the annual examinations according to the years, it is seen that infestation can be seen in any month of any season. Similar to the sampling period in this study, it was reported that L. intestinalis infestation was seen intensively in July, August, and September (Saç et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…The first studies related to this species were done by Başaran and Kelle (1976) and Cantoray and Özcan (1975) in Turkey. Various studies were carried out on this infestation in fish in Turkey (Uzbilek and Yıldız, 2002;İnnal et al, 2007;Demirtaş and Altındağ, 2011;Koyun et al, 2015;Saç et al, 2015) and in the World (Olson et al, 2002;Bouzid et al, 2008a;Hajirostamloo, 2009;Mehraban et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…found in collected samples. As was observed by Saç et al (2016) the difficulty in determine the sex of the infected fish was probably due to absence or degeneration of sexual organs possibly caused by compression or potential inhibition acted by the parasite on development of the reproductive system with diverting gonad development to somatic growth Somayeh DOOSTI and Fevzi YILMAZ 10(4): 2416-2423, 2020 Occurrence Of Ligula Sp. Plerocercoids İn Ladigesocypris İrideus (Ladiges, 1960) From South-Western Turkey: New Host And New Locality Records in infected fish (Arme, 1968;Loot et al, 2002;Cowex et al, 2008;Hoole et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Also, some other studies reported intensity and infection prevalence of parasites by size, sex and seasonal distribution on the host fish species (Kır et al, 2004;Tekin et al, 2006;Kurupınar and Öztürk, 2009;Özbek and Öztürk, 2010;Turgut et al, 2011). In addition, the effect of parasites on physiological and anatomical structures of fish and pathological investigation on infected hosts were also reported (Akmirza, 2007;Korkmaz and Zencir, 2009;Saç et al, 2016;Aydogan et al, 2018).…”
Section: Introductionmentioning
confidence: 93%